O naruszaniu podstawowych zasad postępowania naukowego. “Wzgórze przeznaczenia archeologii” górą skandalu - Kolb, Frank (Poznańskie Towarzystwo Przyjaciół Nauk, 2014)
The article discusses ethical aspects and thoroughness of scientific research on the example of German excavations in Troy, conducted in 1988 by a team from Tübingen University. The author demonstrates how archaeologists became entangled in various relationships with polictical and economic circles, which subsequently yielded an interpretation of findings which ensured financial and media support. The text is an emphatic call for independence and objectivity of scientific investigations that should remain free of any pressure. Although the paper relies on an example from the milieu of archaeologists. historians and classical philologists, the appeal of the authors is a universal one.
On violating fundamental principles of scientific conduct. “Archaeology’s hill of destiny” a mountain of scandal1.
„We are paying a high price for the increasingly unequivocal equation drawn between knowledge and science and ordinary market product. The ideal of perfectly unrestrained cognition, the true mother of science, is threatened by the mass drive towards practical use and application of knowledge, a looming departure into nothingness. Politicians and managers of scientific life are guilty of considerable contribution in corrupting respectable university structures, and thus undermining culture of science and scholarly ethics. (…). Acquisition of funds, sponsorship, media presence, popularisation or even striving for commercial gain are recognised by politicians and scientific consultants, but most of all they are accepted by the university management as objectives worthy of effort, not to say the foremost goals of science. University rectors are nowadays interested primarily in the amounts of acquired moneys. The outcomes of research thus financed is subject to virtually no control, nor does it arouse any interest, unless it turns out to be fit to be announced in the media as a sensation, thereby serving the ‘prestige’ of the university”.
Keywords: Troy; archaeology; Homer; Iliad; Trojan war; myth of Troy; media; politics; economy; manipulation